Impact of Government Expenditure on Economic Growth in Nigeria: 1970-2020 - Ibrahim Musa; Yahaya Ismail (International Journal of Management and Business Applied, 2023)
In this study, the impact of government expenditure on Nigeria's economic growth rate from 1970 to 2020 is analyzed. OLS was used to estimate the connection between the variables over the long run. The findings show a positive link between the Log of Gross Domestic Products (LGDP’s) log and its initial lag, which is statistically significant. The result reveals a positive association between the (LGDP) and the log of recurrent government expenditure (RGE), as well as between the (LGDP) and the log of first lag of recurrent government expenditure (RGE). A positive link exists between the (LGDP) and the log of capital government expenditure (CGE), but a negative relationship exists between the (LGDP) and the log of first (CGE). The link between the (LGDP) and the domestic debt of the federal government (LFGDD) is inverse, while the relationship between the logs of the first lag of the domestic debt of the federal government (LFGDD) is positive. The R2 determination coefficient is 0.698968. The outcome demonstrates that explanatory factors account for 70% of the variation in the (LGDP). The model is acceptable since the F-statistic 3595.905 with a probability of 0.000000 is significant at 1%. The long-term trend of the explanatory variables, which has increased since the year 1985, is linked to GDP. The outcome presented above also depicts the predicted short-run relationship. Therefore, it is recommended that government expenditure be examined and bolstered to have a positive impact on Nigeria's growth rates.